BUDAYA LITERASI MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS PGRI ADI BUANA SURABAYA - Ahmad Fais; Ira Eko Retnosari (Buana Bastra, 2020)
This study is based on the habits and lack of interest of students who have not been able to fulfill their duties and responsibilities maximally, especially reading and writing. This is due to the students' habits compared to the culture of literacy, and the characteristics of students with backgrounds of thinkers, workers, organizational activists and mediocre ones. This study aims to reveal the habits of students PBSI in terms of literacy and kelisanan, both to meet the needs of the task as a student or for other purposes such as to fill the spare time. This research uses descriptive qualitative method. This research data is the result of student activity done inside and outside campus. Based on the result of the research, it can be concluded that the student literacy culture of PBSI Unipa Surabaya in this research is still "low", because the result of the research has been done, there are 24, 28, and 35 students reading books in 1 day, 1 month. While There are 25 writing poems, 17 short stories and 19 students who have interest to write articles. Students of PBSI Unipa Surabaya also have different characteristics. They have the character of thinkers, idlers, workers, and organizational activists.